Aspirin and coronary artery disease - Maree, Andrew O.; Fitzgerald, Desmond J. (Thrombosis and Haemostasis, 2004)
Coronary atherosclerosis (CAD), a chronic inflammatory disorder, arises when genetic susceptibility, intercurrent conditions such as diabetes and hypertension and environmental factors interact. Although CAD can remain stable for many years, thrombus formation at sites of plaque rupture may lead to unstable angina (UA) or myocardial infarction (MI). Already recognised as the central component of coronary thrombosis, platelets, through their interaction with monocytes and endothelial cells, may also be involved at the earliest stages of atheromatous plaque evolution. Aspirin, the prototype antiplatelet agent, covalently and irreversibly inhibits cyclooxygenase (COX) and thus inhibits platelet thromboxane (TX) A2 biosynthesis. Anti-oxidant properties and the ability to modulate transcription of immunologically important genes have also been attributed to aspirin. Non-selective COX inhibition, however, predisposes to bleeding, predominantly secondary to dosedependent gastro-intestinal toxicity. The emerging concept of “aspirin resistance” coincides with the development of alternative antiplatelet therapy and point-of-care platelet function assays. Though variable aspirin pharmacokinetics may explain many cases, heritable factors, inducible platelet COX expression and isoprostane formation may also contribute. In future, risk factor screening and point-of-care platelet function assay may identify vulnerable patients who would benefit from additional or alternate antiplatelet therapy.
Keywords: Atherosclerosis; coronary thrombosis; antiplatelet; aspirin resistance; heritable